Maqa̅Ṣid Al-Mu’a̅Malah Dalam Fatwa DSN-MUI Tentang Dropship - Mustika Sari, Yunita Dwi; Nursobah, Achmad; Khasanah, Fitrohtul (ITB AAS INDONESIA Surakarta, 2024)
This study discusses the DSN-MUI fatwa regarding the dropship business practice from the sharia perspective using the maqashid al-muamalah approach. Dropship is an innovative business concept where merchants sell goods to customers without stocking inventory. Although the DSN-MUI Fatwa has provided legal guidance regarding dropshipping, understanding the Sharia principles underlying this Fatwa remains inadequate. The aim of this research is to evaluate the maqashid al-muamalah dimensions introduced in the DSN-MUI Fatwa on dropship and to understand its consequences and relevance within the framework of sharia economics and law. The research method employed is literature review, involving the collection and review of the DSN-MUI Fatwa on dropship and related literature on dropship and maqasid al-mu’amalah. The findings indicate that the DSN-MUI Fatwa reflects characteristics and principles relevant to the maqashid al-muamalah dimensions, such as sustainability, transparency, stability, protection, and justice. The fatwa aims to regulate dropship practices fairly, transparently, and in accordance with sharia values in the context of modern economics. This research provides practical guidance for merchants, consumers, and religious authorities involved in dropship. It is hoped that this research will strengthen the sharia legal framework related to modern business in the context of the global economy and enhance understanding of dropship practices from the perspective of maqashid al-muamalah